Desproporcionalidade da representaç\~ao na câmara dos deputados: Análise dos efeitos sobre o sistema partidário no Brasil - Pedro Cavalcante; Mathieu Turgeon (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper offers a systematic and comprehensive analysis of the effects of malapportionment on partisan bias, that is, the uneven distribution of legislative seats among parties for votes received. Specifically, it examines such effect in the Brazilian Lower Chamber from 1994 to 2010. First, we use King's (1990) multinomial bilogit model to analyze the responsiveness of the Brazilian electoral system, which revealed to be quite high. Second, adapting the analytical strategy of Grofman, Koetzle e Brunell (1997) to multi-party system and multi-member districts, and after extracting the effects of electoral coalitions, we found results that suggest strong malapportionment effects on partisan bias in Brazil. These effects, however, vary considerably by parties and elections.
Keywords: D72; 330; malapportionment; party system; coalitions; Chamber of Deputies; Brazil